AI's Healing Touch: Examining Machine Learning's Transformative Effects on Healthcare - Alexandra Harry (BULLET : Jurnal Multidisiplin Ilmu, 2023)
In the field of healthcare, artificial intelligence (AI) has emerged as a paradigm-shifting force, upending established procedures and promising unmatched improvements. This in-depth analysis examines the varied ways in which AI is being used in healthcare, focusing on its transformational potential, the difficulties it presents, and the crucial ethical issues that must be taken into account when it is used. Through a number of topic categories, the article opens by highlighting the vast range of AI's impact on healthcare. Each section delves into a specific aspect of AI's influence, illuminating subjects including clinical decision-making, customized medicine, diagnostic accuracy, and drug discovery. The complex interaction between AI and medical imaging is revealed, as well as the possibility for AI systems to examine enormous datasets. The promise of AI in changing clinical decision-making is further examined in the article, with a focus on its role in patient management and its capacity to overcome ethical dilemmas. The ethical environment that surrounds AI-driven healthcare is a major area of focus. The study highlights the value of protecting patient data privacy and the necessity of secure data transmission and compliance with data protection laws. It also addresses the widespread worry about bias in AI algorithms, highlighting the necessity of objective training data and rigorous bias detection procedures. When openness and accountability are pitted against the complexity of complicated algorithms, the interpretability of AI-generated insights becomes a problem. The assessment looks more closely at the moral issues surrounding patient autonomy and the changing responsibilities of healthcare providers. It advocates for open communication between AI, patients, and healthcare practitioners as it navigates the complex balance between innovation and patient welfare. The article also emphasizes the need for strong ethical frameworks and rules to appropriately govern AI implementation in healthcare. The thorough investigation ends with an analysis of the potential applications of AI in healthcare. It describes the possibility for improved medical operations, drug discovery, remote patient monitoring, and diagnostic improvement. In order to leverage AI's transformative potential while protecting patient interests, healthcare practitioners, data scientists, policymakers, and ethicists must work together. This is highlighted in the abstract. The review captures the remarkable change AI has brought about in healthcare. The study emphasizes the critical need of simultaneously exploiting AI's promise and attending to the ethical and regulatory issues that arise as technology develops and AI becomes more integrated. In the end, the abstract presents a comprehensive picture of AI's changing healthcare role and its potential to transform patient care, medical procedures, and the entire structure of the healthcare sector.